The Seasional Trends of Dissolved Oxygen and pH in Sugihan River, South Sumatra, Indonesia - Noormaisyah Saleh; Risfidian Mohadi; Agus Dwi Saputra (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2016)
Abstract: The concentrations of DO and pH of Sugihan Rivers from the upstream at Riding, Pangkalan Lampam, OKI to the offshore region of Sugihan Estuary were analyzed at 15 sampling points during dry and rainy seasion. All measurements of DO and pH were direct analysis at the river stream. The concentrations as the average values of DO in dry seasion was 1,97 mg / L while in rainy seasion was 2,57 mg / L, and for the pH degree was 3,63 in dry seasion and 4,04 in rainy seasion, respectively. Based on the DO and pH values, this study shown the natural forests and peat lands gave contribution to the low of pH degree. The low of DO values also influenced by the pH, because decomposition in the peatlands made higher solubility of biomass to the rivers stream and decreasing the ability of oxygen to penetration into the waterbody.Keywords: DO, pH, Sugihan river, natural forest, peatland Abstrak (Indonesian): Konsentrasi DO dan pH Sungai Sugihan dari hulu di Kuda, Pangkalan Lampam, OKI ke wilayah lepas pantai Sugihan Muara dianalisis pada 15 titik sampling selama musim kering dan hujan. Semua pengukuran DO dan pH adalah analisis langsung di aliran sungai. Konsentrasi sebagai nilai rata-rata DO di musim kering adalah 1,97 mg / L sedangkan di musim hujan adalah 2,57 mg / L, dan untuk tingkat pH adalah 3,63 di seasion kering dan 4,04 di musim hujan. Berdasarkan nilai-nilai DO dan pH, penelitian ini menunjukkan bahwa hutan alam dan lahan gambut berkontribusi pada rendahnya tingkat pH. Rendahnya nilai DO juga dipengaruhi oleh pH, karena dekomposisi di lahan gambut membuat kelarutan yang lebih tinggi dari biomassa ke aliran sungai dan penurunan kemampuan oksigen untuk penetrasi ke aliran sungai tersebut. Kata kunci: DO, pH, Sungai Sugihan, hutan alam, lahan gambut